2001
DOI: 10.1097/00007435-200104000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of External Genital Warts in Men Using 5% Imiquimod Cream Applied Three Times a Week, Once Daily, Twice Daily, or Three Times a Day

Abstract: In this study, the optimal dosage regimen was the approved three times a week regimen. More frequent application (up to three times a day) did not improve clearance and was associated with an increase in local adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 16 publications
2
45
0
5
Order By: Relevance
“…Meta-analysis of the studies by Fife et al 129 and Trofatter et al 134 found no statistically significant differences between imiquimod 5% cream applied three times weekly, once daily or twice daily (all possible comparisons) (forest plot presented in Appendix 7).…”
Section: Complete Clearance At Another Time Pointmentioning
confidence: 99%
See 4 more Smart Citations
“…Meta-analysis of the studies by Fife et al 129 and Trofatter et al 134 found no statistically significant differences between imiquimod 5% cream applied three times weekly, once daily or twice daily (all possible comparisons) (forest plot presented in Appendix 7).…”
Section: Complete Clearance At Another Time Pointmentioning
confidence: 99%
“…58 Studies were identified evaluating application of imiquimod 5% for 4, 8, 12 and 16 weeks 130,133 and at application schedules of once daily, twice daily and three times daily. 129,134 After consultation with clinical experts on the potential influence of treatment duration, dose and formulation (relates to ease of application) on clinical effectiveness, the following assumptions were made for the purposes of carrying out meta-analysis, both direct and indirect:…”
Section: Interventions and Comparatorsmentioning
confidence: 99%
See 3 more Smart Citations